Thrombotic thrombocytopenic purpura - a disease with multiple organ manifestations. Diagnostic and therapeutic difficulties in clinical practice - Magdalena Szydełko; Joanna Szydełko; Agnieszka Szymczyk; Dominika Szymczyk; Magdalena Chomczyńska; Monika Podhorecka (Kazimierz Wielki University, 2018)
Introduction: Thrombotic thrombocytopenic purpura (TTP) is a rare, heterogeneous and life-threating disease requiring prompt differential diagnosis. The most common form of that disease is idiopathic form affects usually young adults. The etiopathogenesis is most likely based on the excessive formation of platelet aggregates and microthrombosis in small vessels, capillaries due to the deficiency of a specific enzyme, ADAMTS13 (disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13). Aim of the study: The aim of this review was to present the diagnostic difficulties of the TTP, which are mainly related to the range of multi-organ deficiency and symptoms that resemble lots of other diseases. Moreover, we discussed the current, as well as future perspectives of the treatment of thrombotic thrombocytopenic purpura. Description of knowledge: The principal symptoms, which occur in TTP patient are caused by microangiopathic hemolytic anemia and thrombocytopenia. Moreover, that disease may also manifest by neurological, renal, cardiac abnormalities as well as abdominal disturbances, fever and flu-like symptoms. The other thrombotic microangiopathies, especially hemolytic-uremic syndrome, immune-mediated diseases, infections, stroke, myocardial infarction should be taken initially in the differential diagnosis. The current management is based on plasma exchange therapy, steroids, rituximab, but the novel methods are investigated. Conclusions: The differential diagnosis of hematological patients presenting clinical symptoms of thrombocytopenia, anemia associated with multi-organ dysfunction, especially when we suspect an autoimmune background of a given disease is crucial to implement the appropriate therapy and save the patient's life.